SOSIALISASI SOFT CHEWY COOKIES BEBAS GLUTEN DAN KASEIN UNTUK ANAK AUTIS: indonesia - nadya putri ramadhani (Poltekkes Kemenkes Bengkulu, 2026)
Children with Autism Spectrum Disorder (ASD) are often sensitive to gluten and casein, which can worsen digestive and behavioral issues. A gluten-free casein-free (GFCF) diet is commonly used as a nutritional approach, but suitable food options remain limited. This community engagement activity aimed to improve the understanding of parents and teachers of children with ASD regarding the GFCF diet and to introduce an alternative snack made from local ingredients—soft chewy cookies based on MOCAF (Modified Cassava Flour) and purple sweet potato flour. The activity was carried out through a socialization event on May 2, 2025, at Sinar Hafizah Special Needs School (SLB) in Gedong Tataan-Pesawaran, using a participatory approach. The materials presented included basic knowledge about ASD, the importance of the GFCF diet, and the nutritional benefits and potential of local ingredients as safe and healthy food alternatives for children with ASD. The session received enthusiastic responses, as evidenced by active discussions and positive feedback. This activity demonstrates that local food-based education can be an effective strategy in supporting GFCF dietary practices and promoting sustainable food independence for families with special needs children.